Porokeratosis mibelli- A Case Report - Siddiqui, MA; Kabir, MR; Badruddoza, SM; Amin, AA (TAJ: Journal of Teachers Association, 2009)
A twelve years old girl of class VII reported at skin & VD out patient department of Rajshahi Medical college Hospital in November 2003 with multiple small pink to violeceous non pruritic patches extending from medial aspect of left ankle joint to the medial aspect of left thigh in a linear fashion. The individual lesions are small-circumscribed patches having hyperkeratotic margin and central atrophy. The raised hyperkeratotic margin contains on its top a furrow along the course of the wall. The surface was verrucous and many of the lesions have serpiginous border. Near the ankle joint and below the ankle joint individual lesion forms zosteriform groups. On the thigh the lesions are linear. Some small satellite lesions are also present. All the lesions are hairless and anhidrotic. The onset of the individual lesions was at the age of six years, near the ankle joint. Lesions enlarge slowly and progressed to upward direction in a linear fashion. Skin biopsy for histopathology revealed the picture of porokeratosis. doi: 10.3329/taj.v17i2.3457 TAJ 2004; 17(2): 106-107